The experimental realization of high-fidelity 'shortcut-to-adiabaticity' quantum gates in a superconducting Xmon qubit. (20th June 2018) - Wang, Tenghui; Zhang, Zhenxing; Xiang, Liang; Jia, Zhilong; Duan, Peng; Cai, Weizhou; Gong, Zhihao; Zong, Zhiwen; Wu, Mengmeng; Wu, Jianlan; Sun, Luyan; Yin, Yi; et al.
Abstract: Based on a 'shortcut-to-adiabaticity' (STA) scheme, we theoretically design and experimentally realize a set of high-fidelity single-qubit quantum gates in a superconducting Xmon qubit system. Through a precise microwave control, the qubit is driven to follow a fast 'adiabatic' trajectory with the assistance of a counter-diabatic field and the correction of derivative removal by adiabatic gates. The experimental measurements of quantum process tomography and interleaved randomized benchmarking show that the process fidelities of our STA quantum gates are higher than 94.9% and the gate fidelities are higher than 99.8%, very close to the state-of-art gate fidelity of 99.9%. An alternate of high-fidelity quantum gates is successfully achieved under the STA protocol.